Improvement in NO2 Sensing Properties of Semiconductor-Type Gas Sensors by Loading of Au Into Porous In2O3 Powders - Ueda, Taro; Ishida, Keijiro; Kamada, Kai; Hyodo, Takeo; Shimizu, Yasuhiro (Frontiers in Materials, 2019)
Porous (pr-) In2O3 powders loaded with and without noble metals (Au, Pd, or Pt) were prepared by ultrasonic spray pyrolysis employing the PMMA microspheres as a template (typical particle size (ps): 28 or 70 nm with a diameter), and their NO2 sensing properties were examined. The Au loading on the pr-In2O3 was effective to increase the NO2 response at lower operating temperature (≤200°C), while the metal loading of Pd or Pt were hardly effective. In addition, a decrease in the PMMA microspheres (from 70 to 28 nm in ps) largely increased the NO2 response, and an optimized amount of Au loaded on the pr-In2O3 sensor was 1.0 wt%. The decrease in the thickness of the sensing layer improved the NO2 response and response speed. It was suggested that the Au loading enhanced the amount of the negatively adsorbed NO2 on the bottom part of the sensing layer, leading to the increase in the NO2 response. Furthermore, the introduction of additional macropores (ps: 150 nm) to the 1.0 wt% Au loaded pr-In2O3 sensor increased the response to a low concentration of NO2 (0.025 ppm) at 30°C. Therefore, it was found that easy gas diffusion from the surface to the bottom part of the sensing layer increased the effective concentration of NO2, and thus the NO2 response was increased.